FANATISME FANS SEPAK BOLA DALAM MENDUKUNG PERSEBAYA SURABAYA DI MEDIA SOSIAL INSTAGRAM @GREENNORD.27 - Pratiknyo, Tiar Yogo; Tranggono, Didiek (Jurnal Ilmiah Wahana Pendidikan, 2024)
Football is the most popular sport throughout the world, including in Indonesiaitself. In Indonesia itself, there is also a league which is participated by teams, oneof which is Persebaya Surabaya. Persebaya also has fans called dolls. Bonek is aPersebaya fan who always provides support by supporting directly by going to thestadium or watching on television and buying attributes. These dolls always supportthem totally, which shows their inner fanaticism. Even though some of these dollscannot see directly, they can use Instagram social media. Instagram@greennord.27 is one of the largest fanbases managed by the Green Nord 27community. This research aims to find out the forms and factors that causefanaticism on Instagram social media and to see the views of fanaticism amongPersebaya supporters from a Communication Science perspective. This researchuses social identity theory, symbolic interactionism, and fanaticism theory using qualitative methods with a descriptive analysis approach. Data was taken using in-depth interviews and documentation, where the informants were Persebaya fans who follow the Instagram account @greennord.27 and always follow Persebayadevelopments. The results of this research show that Persebaya fans havefanaticism on social media, namely always taking the time to watch matches,always uploading activities after watching live on Instagram Story using attributes,following official Persebaya accounts and Persebaya players, uploading matchscores on the media. social, and always following Persebaya developments.